Cell cycle regulator, small silencing RNA, and segmentation patterning gene expression in relation to embryonic diapause in the band-legged ground cricket. (November 2018) - Shimizu, Yuta; Tamai, Takaaki; Goto, Shin G.
Abstract: Insects enter diapause to synchronize their life cycle with biotic and abiotic conditions favorable for their development, reproduction, and survival. Adult females of the band-legged ground cricket Dianemobius nigrofasciatus (Orthoptera, Glyllidae) respond to environmental factors in autumn and lay diapause-destined eggs. The eggs arrest their development and enter diapause at a very early embryonic stage, specifically the cellular blastoderm. To elucidate the physiological mechanisms underlying this very early stage programmed developmental arrest, we investigated the cell division cycle as well as the expression of cell cycle regulators, small silencing RNAs, and segment patterning genes. The diapause embryo arrests its cell cycle predominantly at the G0 /G1 phase. The proportion of cells in the S phase of the cell cycle abruptly decreased at the time of developmental arrest, but further changes of the G0 /G1 and G2 /M were later observed. Thus, cell cycle arrest in the diapause embryo is not an immediate event, but it takes longer to reach the steady state. We further elucidated molecular events possibly involved in diapause preparation and entry. Downregulation of Proliferating cellular antigen ( PCNA ; a cell cycle regulator), caudal and pumilio ( cad and pum ; early segmentation genes) as well as P-element induced wimpy testis ( piwi ) (a small silencing RNA) prior to the onset of developmental arrest was notable. The downregulation of PCNA, cad and pum continued even after entry into developmental arrest. In contrast to upregulation in non-diapause eggs, Cyclin D (another cell cycle regulator) and hunchback, Krüppel, and runt (gap and pair-rule genes) were downregulated in diapause eggs. These molecular events may contribute to embryonic diapause of D. nigrofasciatus . Graphical abstract: Highlights: Dianemobius nigrofasciatus crickets in diapause arrest their development at the cellular blastoderm stage. The diapause embryo arrests its cell cycle predominantly at the G0 /G1 phase. Suppression of a cell cycle regulator and a small silencing RNA gene was notable prior to developmental arrest. Several segmentation genes are downregulated before and after entry into developmental arrest. These molecular elements would contribute to the developmental arrest at the very early embryonic stage.